Rancang Bangun Sistem Informasi Pengendalian Persediaan Barang Pada UD. Mekaryo Utomo Lamongan - Suhariyanto, Dedy; Tanuwijaya, Haryanto; Setyawan, Henry Bambang (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
UD. Mekaryo Utomo is trade enterprises which is engaged in the sale of building materials. In business development UD. Mekaryo Utomo use the warehouse as a place to store inventory. Processes that are currently running to include the process of ordering, receiving, the process of expenditures, and reporting processes. The development of technology can be utilized to create a solution to assisting in the application of UD. Mekaryo Utomo in performing inventory control that will assist in the administration of recording entry and exit of goods, supervision of the inventory in the warehouse to ensure service to customers, accelerating in making the reports required by management. Based on the results of the previous discussion, it can be concluded from this study produced an information system for monitoring entry and exit of goods in the warehouse. determine the quantity and at the right time to make orders to suppliers, and may provide the reports required by the management quickly and accurately.